Genesis of the term "savilaida": from collections of avant-garde poetry till Lithuanian neologism - Egidijus Jaseliūnas (Lietuvos Istorijos Studijos)
The genesis of the Lithuanian neologism "savilaida" has not been studied by the science of history, though such studies would allow reasonable answering to the questions of expedience of the usage of the term and uniqueness of its object. The article aims at analyzing the history of the origin of the Lithuanian term "savilaida" and its genesis in the Soviet society.